Human Endogenous Retrovirus K(HML-2) Gag- and Env-Specific T-Cell Responses Are Infrequently Detected in HIV-1-Infected Subjects Using Standard Peptide Matrix-Based Screening - Jones, R. Brad; John, Vivek M.; Hunter, Diana V.; Martin, Eric; Mujib, Shariq; Mihajlovic, Vesna; Burgers, Peter C.; Luider, Theo M.; Gyenes, Gabor; Sheppard, Neil C.; SenGupta, Devi; Tandon, Ravi; et al. (Clinical and Vaccine Immunology, 2012)
Classifications Services CVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue CVI About CVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy CVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1556-6811 Online ISSN: 1556-679X Copyright © 2014 by the American Society for Microbiology. For an alternate route to CVI .asm.org, visit: CVI